AUDIOVISUEL DE KISANGANI : RECHERCHE DES ASYMETRIES DANS LES ROLES DES ACTEURS - Damas ESOLE KESOLE KAYA, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The wind of gender equality is currently blowing in all sectors of national life. Obviously, that of the audio-visual of Kisangani puts aside this dynamic. The diagnosis of inhibitory factors having already been made in a previous survey, the present attempts to identify the resulting asymmetries and delay the beginning of the long struggle for parity against this kind of inequalities long criticized. The findings of this study indicate that these atavisms are apparent in terms of digital representation, distribution of roles, material benefits to be gained and psychological in the hands of media professionals. Thus, the purpose of this article is to propose a way out of these asymmetries to allow targeted media to leave the stage of formal gender parity for that of the actual gender parity.